The Implementation of Geogebra-Assisted Discovery Learning Approach Towards Mathematical Communication Ability of Vocational Students - Danny, Firman; Jaenal, Enjang; Fauzy, Alwan; Sugandi, Asep Ikin; Afrilianto, M. (IKIP Siliwangi, 2024)
Mathematicals communication ability is one of essential mathematical abilities that every person, who learns mathematics, needs to have. However, many facts found in many studies has shown us that students’ achievements on this ability are still low. Factors that may cause it spread from teacher factors, tools, approaches, learning media to students themselves. To overcome these issues, many efforts are made to select and implement learning approaches that can improve students' mathematical communication ability as well as their activities in instructional process. Thus, the purpose of this study is to examine whether the implementation of GeoGebra-assisted discovery learning approach is effective in improving vocational school students' mathematicals communication ability or not. This quasi experimental research design involved 60 students of Gema Karya Bahana Vocational School as samples. The samples were divided into two groups in which 30 students of Accounting-1 class as the experimental group and 30 students of Accounting-2 as the control group. The data collected through a description test consisted of 3 questions on a linear program. The data collected through the test, both in pre-test and post-test, then analyzed using inferential statistics. The results of this analysis showed that the implementation of the discovery Learning approach assisted by GeoGebra was effective in improving vocational school students' mathematicals communication ability. Thus, the discovery learning approach assisted by GeoGebra can be implemented on instructional processes as one of instructional approach alternatives.